Upaya Meningkatkan Hasil Belajar Siswa Dalam Materi Iman Kepada Qada' Dan Qadar Dengan Model Problem Based Learning Di Kelas IX-1 Smpn 2 Panti - Isnaemi, Ahmad (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the application of the Problem Based Learning (PBL) model in improving students' understanding of the concept of Iman to Qada' and Qadar in class IX-1 of SMPN 2 Panti. The method used is Classroom Action Research (CAR) with two cycles, involving planning, implementation, observation, and reflection. The results show that in the first cycle, students faced difficulties in understanding the material and actively participating in discussions. However, in the second cycle, there was a significant improvement in participation, discussion quality, and students' evaluation test results. The application of the PBL model has proven to be effective in improving students' understanding of Iman to Qada' and Qadar, as well as encouraging critical and collaborative thinking. In conclusion, PBL is an effective method for enhancing the quality of religious education in class IX-1 SMPN 2 Panti.